2016
DOI: 10.1007/s00382-016-3096-5
|View full text |Cite
|
Sign up to set email alerts
|

Winter climate changes over East Asian region under RCP scenarios using East Asian winter monsoon indices

Abstract: that resemble the composite strong winter monsoon pattern are simulated more or less weakly in CMIP5 compared to the observation. However, the regressed fields of sea level pressure, surface air temperature, 500-hPa geopotential height, and 300-hPa zonal wind are well established with pattern correlations above 0.83 between CMIP5 and observation data. The differences between RCPs and Historical indicate strong warming, which increases with latitude, ranging from 1 to 5 °C under RCP4.5 and from 3 to 7 °C under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
3
15
0
Order By: Relevance
“…The pre‐1920s increase and the post‐1920s decrease in our coral‐based PP record for the NSCS correspond to the strengthening and the weakening, respectively, of the EAWM during these periods. Studies based on coupled models have suggested that the EAWM may weaken in the future because of the reduction in the land‐sea thermal contrast under emissions‐driven global warming scenarios (Hong et al, ; Hori & Ueda, ; Hu et al, ). Therefore, the PP in the NSCS will likely decrease in the coming decades due to the projected weakening of the EAWM, and this decrease may significantly impact the marine ecosystem and the biogeochemical cycles in the NSCS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pre‐1920s increase and the post‐1920s decrease in our coral‐based PP record for the NSCS correspond to the strengthening and the weakening, respectively, of the EAWM during these periods. Studies based on coupled models have suggested that the EAWM may weaken in the future because of the reduction in the land‐sea thermal contrast under emissions‐driven global warming scenarios (Hong et al, ; Hori & Ueda, ; Hu et al, ). Therefore, the PP in the NSCS will likely decrease in the coming decades due to the projected weakening of the EAWM, and this decrease may significantly impact the marine ecosystem and the biogeochemical cycles in the NSCS.…”
Section: Resultsmentioning
confidence: 99%
“…because of the reduction in the land-sea thermal contrast under emissions-driven global warming scenarios (Hong et al, 2016;Hori & Ueda, 2006;Hu et al, 2000). Therefore, the PP in the NSCS will likely decrease in the coming decades due to the projected weakening of the EAWM, and this decrease may significantly impact the marine ecosystem and the biogeochemical cycles in the NSCS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the surface meridional wind strength index, the ensemble mean of CMIP3 and CMIP5 models shows a weakening (strengthening) East Asian winter monsoon circulation north (south) of approximately 25°N, associated with the northward shift of the Aleutian Low, and decreased northwest-southeast thermal and sea level pressure differences across Northeast Asia (Jiang and Tian 2013). The CMIP5 MME projects significant intensification and a northward shift of the Aleutian Low, associated with strong warming over the high-latitude North Pacific owing to a reduction of sea ice in the Bering Sea and the Okhotsk Sea (Ogata et al 2014;Hong et al 2016;Xu et al 2016). A cyclonic circulation anomaly north of 40°N and an anticyclonic anomaly south of 40°N in the North Pacific are consistent with the positive trend of the AO.…”
Section: (2) East Asian Monsoonmentioning
confidence: 99%
“…The performances of the models in the Coupled Model Intercomparison Project phase 5 (CMIP5) in simulating EAWM are better than those in CMIP3 [23]. The multimodel ensemble (MME) of CMIP5 models is able to reproduce the overall characteristics of EAWM very well [24,25], although the climatological strength of the EAT is overestimated by most of the models [23,24]. However, the performances of CMIP5 models in the variation of EAT are unclear.…”
Section: Introductionmentioning
confidence: 99%